Enhanced surgical planning with 3D modeling in pediatric surgical oncology: management of complex abdominal tumors in a low-income country - Bautista Hernández, Ivan; Ponce de León Camargo, Daniella Andrea; Zarazúa Orozco, Luis Felipe; Ellis Irigoyen, Andrea; Vega Vega, Ma de Lourdes (International Journal of Research in Medical Sciences, 2025)
Three-dimensional (3D) modeling has emerged as a valuable tool in pediatric oncologic surgery, particularly for complex abdominal tumors where precise anatomical planning is critical. It enables enhanced surgical visualization, improved team communication, and more accurate estimation of vascular structures and adjacent organs, thereby increasing the safety and feasibility of extensive resections. We present six pediatric cases of complex abdominal tumors, including a NOS hepatic tumor, myofibroblastic tumor, cholangiocarcinoma, hepatoblastoma, neuroblastoma, and a Frantz-Gruber tumor, where 3D reconstruction and printing were employed to support preoperative planning and intraoperative navigation. All patients underwent contrast-enhanced thoracoabdominal CT, angiography, and 3D modeling due to tumor size, anatomical complexity, and vascular involvement. Additionally, we performed a literature review to contextualize the clinical value of 3D modeling in pediatric surgical oncology. Six patients underwent complete resections without complications. One patient was deemed unresectable after a detailed 3D evaluation, and only one patient presented a postoperative complication. The models were used to assess tumor boundaries, vascular proximity, and residual liver volume. They also improved interdisciplinary coordination and communication with families. 3D modeling facilitates individualized surgical planning, enabling more accurate, safer, and potentially curative interventions in patients with complex tumors. It enhances communication across the surgical team, supports medical education, and minimizes potential complications. As this technology becomes more accessible, it has the potential to significantly improve outcomes in pediatric surgical oncology.